2017
DOI: 10.3389/fcimb.2017.00007
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing N-acyl Homoserine Lactones-SdiA Suppresses Escherichia coli-Pseudomonas aeruginosa Conjugation through Inhibiting traI Expression

Abstract: Conjugation is a key mechanism for horizontal gene transfer and plays an important role in bacterial evolution, especially with respect to antibiotic resistance. However, little is known about the role of donor and recipient cells in regulation of conjugation. Here, using an Escherichia coli (SM10λπ)-Pseudomonas aeruginosa (PAO1) conjugation model, we demonstrated that deficiency of lasI/rhlI, genes associated with generation of the quorum sensing signals N-acyl homoserine lactones (AHLs) in PAO1, or deletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 46 publications
1
41
1
Order By: Relevance
“…Hence, the targeted activity and corresponding deletion strains have increased growth sensitivity compared to a genome-wide set of deletion strains. We have previously applied chemogenomic profiling to identify biological pathways targeted by an FDA-approved drug, auranofin, and a molecule in clinical trials, ebselen, which were found to possess antifungal activity 37, 38 . Utilizing this approach, 34 heterozygous diploid deletion strains were sensitive to 4b (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Hence, the targeted activity and corresponding deletion strains have increased growth sensitivity compared to a genome-wide set of deletion strains. We have previously applied chemogenomic profiling to identify biological pathways targeted by an FDA-approved drug, auranofin, and a molecule in clinical trials, ebselen, which were found to possess antifungal activity 37, 38 . Utilizing this approach, 34 heterozygous diploid deletion strains were sensitive to 4b (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Given 4b ’s promising antifungal activity in vitro , combined with its potent antivirulence activity against C. albicans hyphae and biofilm formation, it was critical to evaluate whether the compound’s activity could be retained in vivo. C. elegans is an excellent animal model for early-stage evaluation of promising anti-infective and antivirulence agents prior to evaluating agents in mammalian models such as rodents 38, 4346 . A challenge of translating antifungal compounds to clinical applications are issues pertaining to toxicity and rapid metabolism.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations